Pergolakan Pemikiran Ummah (The Unrest Ideas of the Ummah) - Safei, Su'aidi (Terengganu State Foundation Printing, 1991)
Partisan divisions acknowledge the fact the level of bigotry and community awareness is increasingly melting and eroded. It is a wrong approach to label one particular political party or group as Islamic. Here's the grass root of the division among the Muslims, because when we label Islam to any one party, then it seems that Islam belongs to that group only.